Relationship between cell envelope ultrastructure and the antibacterial properties of a novel hydrophobic eumelanin-inspired derivative - Reed, Daniel R.; Nehmzow, Katherine; Essandoh, Martha A.; Ebqa'ai, Mohammad A.; Nelson, Toby L.; Lutter, Erika I.; Cook, Gabriel A.; Champlin, Franklin R. (Frontiers in Bacteriology, 2023)
Introduction: Unique impermeability properties of the gram-negative outer cell envelope typically render these organisms intrinsically resistant to hydrophobic antibacterial compounds. Eumelanininspired indoylenephenyleneethynylene (EIPE) compounds possess scaffolding to which functional groups were attached to potentially provide antibacterial properties in the forms of hydrophilic (EIPE-HCl) and hydrophobic (EIPE-1) derivatives. Methods: Standardized disk agar diffusion and microbroth dilution bioassays were employed to assess the susceptibility of disparate gram-negative and gram-positive bacterial pathogens to the two compounds. EIPE-1 mechanisms of action and intrinsic resistance were further investigated turbidimetrically in batch cultures with the aid of the gram-negative outer membrane permeabilizer compound 48/80. Results: Hydrophobic derivative EIPE-1 exhibited a gram-positive antibacterial spectrum, while hydrophilic derivative EIPE-HCl possessed no antibacterial properties. EIPE-1 exhibited minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) values below 2.0 µg/mL against all gram-positive bacteria, including two methicillin-resistant strains. In contrast, MIC/MBC values greater than 128 µg/mL were obtained for all gram-negative bacteria examined. Susceptibility of two strains of the strict anaerobe Clostridioides difficile indicated the EIPE-1 mechanism of action does not require molecular oxygen. Turbidimetric growth curves revealed EIPE-1 induced rapid bacteriolysis for Staphylococcus epidermidis SK01 and Bacillus subtilis ATCC 6633 of Bacillus subtilis ATCC 6633, thereby suggesting a membrane-directed modality. Lastly, the outer membrane permeabilizer compound 48/80 failed to markedly sensitize any of six selected three phylogenetically disparate gram-negative organisms to EIPE-1. Conclusion: These data strongly suggest that the hydrophobic melanin-inspired derivative EIPE-1 inhibits gram-positive bacteria in a cytoplasmic membrane-directed manner independent of oxygen. Moreover, a secondary mechanism may function concomitantly with outer membrane exclusionary properties to underly the intrinsic resistance of gram-negative pathogens.